Practices of sexual education: an analysis in municipal schools in the south of Brazil - Quaresma da Silva, Denise Regina; Ulloa Guerra, Oscar (Education Policy Analysis Archives, 2011)
<span style="font-family: Garamond; color: black; font-size: 12pt; mso-fareast-font-family: Calibri; mso-ansi-language: EN-US; mso-fareast-language: EN-US; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold; mso-bidi-font-family: Arial;" lang="EN-US">This article approaches a characterization of the practices of sexual education in educative institutions in Novo Hamburgo, Rio Grande do Sul, Brazil, where the precocious gestations have a significative extension. We rescued some theoretical contributions to understand the sexual education, specifically from the pos-structuralism, and from current researches about this topic. Besides, we show qualitative results from the interviews with directives and teachers of the fifty six schools of the municipality.